Harry's trees - Cohen, Jon (Mira, 2018)
Harry Crane is an analyst for the US Forest Service, until his wife dies suddenly and he is unable to cope. Leaving his job and his old life behind, Harry makes his way to the remote woods of northeastern Pennsylvania's Endless Mountains. Determined to lose himself, he takes up residence in the woods. Oriana and her mother, Amanda, are struggling to pick up the pieces from their own tragedy. Oriana roams the forest searching for answers, and she believes that Harry is the key to righting her world. Harry reluctantly agrees to help Oriana in a scheme involving a wolf, a stash of gold coins, a fairy tale called The Grum's Ledger, and a wise old librarian named Olive.--